Cyclic glycine-proline administration normalizes high-fat diet-induced synaptophysin expression in obese rats. (August 2019) - Li, Fengxia; Liu, Karen; Wang, Ao; Harris, Paul W.R.; Vickers, Mark H.; Guan, Jian
Abstract: Childhood metabolic disorders are associated with insulin-like growth factor (IGF)-1 deficiency, which can adversely affect brain development and function. As a neuropeptide, cyclic glycine-proline (cGP) improves IGF-1 function in brain and regulates IGF-1 bioavailability in plasma. Whether such a regulatory process mediates the neurotrophic effects of cGP remains unknown. This study examined the effects cGP treatment on synaptic expression and their association with IGF-1, IGF binding protein (IGFBP)-2 and cGP concentrations in the brain of rats with high fat diet (HFD)-induced obesity. Male rats received either a HFD or a standard chow diet (STD) from weaning and were then treated with either saline or cGP from 11 to 15 weeks of age. The concentrations of cGP, IGF-1 and IGFBP-2 were measured in the brain tissues using ELISA and HPLC-MS. The expressions of synaptic markers were evaluated in the hippocampus, hypothalamus and striatum using immunohistochemical staining. Compared to the STD group, IGF-1 and IGFBP-2, but not cGP concentrations, were lower in the HFD groups. The expression of hippocampal synaptophysin, glutamate receptor-1, GFAP and striatal tyrosine-hydroxylase were also reduced in the HFD groups. While treatment did not alter tissue IGF-1, cGP administration that increased the concentration of cGP in brain tissues, normalized the expression of synaptophysin, GFAP and tyrosine-hydroxylase, but not glutamate receptor-1. IGF-1 concentration in brain tissues correlated with the expression of all synaptic markers. HFD feeding reduced synaptic expression and tissue IGF-1 in brains which were closely associated, thus suggesting IGF-1 in the brain is largely bioavailable. Without increasing IGF-1 in the brain, administration of cGP normalized synaptic expression, possibly be mediated through increasing bioavailable IGF-1, but further studies are required to confirm this. Graphical abstract: Unlabelled Image Highlights: cGP is a neuropeptide and improves IGF-1 function in brain. cGP regulates the bioavailability of IGF-1 in plasma, such a regulatory role for cGP in the brain remains unknown. Post-weaning HFD reduced IGF-1concentration and synaptic expression in the brain tissue of young adult rats. Administration of cGP normalized the synaptic expressions, possibly be mediated by improving the bioavailability of IGF-1.